Dual contraceptive use among adolescents and young adults: correlates and implications for condom use and sexually transmitted infection outcomes. Issue 3 (29th November 2013) - Hood, Julia E; Hogben, Matthew; Chartier, Maggie; Bolan, Gail; Bauer, Heidi
Abstract : Background: Simultaneous condom and hormonal contraception usage ('dual method use') maximises protection against pregnancy and sexually transmitted infection (STI), although there is concern that promotion of this strategy could result in diminished condom use and inadvertently increase STI risk. In this study, we (1) assessed how the use of dual methods, versus condoms alone, related to STI and consistency of condom use and (2) described the correlates of dual use. Methods: A sample of 1450 young people aged 12–25 years were surveyed and screened for chlamydia and gonorrhoea at non-clinical sites in two high morbidity Californian counties in 2002–2003. Differences in STI prevalence and reported consistency of condom use were assessed for 'condom only' and 'dual method' users. Correlates of dual use were analysed via multivariate polytomous logistic regression. Results: Condom only and dual method users did not significantly differ in terms of STI prevalence or reported consistency of condom use. Sex, age, race and relationship tenure were significant correlates of dual use. Discussion: In these observational data, dual method use did not detrimentally affect STI risk. If interpreted alongside each subgroups' risk patterns for STI and unplanned pregnancy, the correlates of dual use can inform STI and pregnancy prevention interventions.